POST-CONFLICT STATE (RE)CONSTRUCTION: THE INVOLVEMENT OF CIVIL SOCIETY IN THE BURUNDIAN DEMOCRATIC PROCESSES / LA (RE)CONSTRUCTION DE L’ETAT POST-CONFLIT: L’IMPLICATION DE LA SOCIÉTÉ CIVILE DANS LE PROCESSUS DÉMOCRATIQUE AU BURUNDI - MERABTI, Sarah; MIȘCOIU, Sergiu (Studia Universitatis Babes-Bolyai Studia Europaea, 2015)
The end of the 20th Century inaugurated an era of regime change and democratic fever in Central and Western Africa. Burundi made no exception to this rule, being also strongly affected by the civil wars that took place in its neighboring countries, Rwanda and D.R. Congo. But the complexity of the traditional Burundian society prevented change and postponed it and/or deflected it toward even more authoritative governmental formulas. In this article, we will analyze the contribution of civil society to the contemporary democratic transition in Burundi.